Estimation of Triclosan Concentration in the Wastewater: A Case of Patna Municipal Area - Roy, Sulagna; Maurya, Nityanand Singh (National Academy science letters, 2019)
The increasing concern about the emerging contaminants, especially the endocrine disrupting chemicals, which include pesticides and the pharmaceuticals and personal care products, has stirred up the rate of monitoring their presence in the environment. Triclosan is one such chemical used as an antibacterial and antimicrobial in many personal care products. This chemical is present in very low amounts in the personal care products, but its appearance in the environment becomes a matter of concern due to its detrimental effects on the environment. Therefore, this paper focuses on determination of Triclosan concentration in the personal care products used by the residents of Patna municipal area. It also focuses on finding out the ultimate load of Triclosan discharged and its corresponding concentration in the wastewaters of Patna.